Interview with Jaume Funes Arriaga (Journal of Parents and Teachers, 2014)
Jaume Funes is a psychologist, educator and journalist. He is specialised in childhood and its social difficulties. He states that the kid is institutionally and socially mistreated and also that education comes from home and it is complemented at school. It can not be expected that school is the only institution which works for the kids’ education because kids need security to grow healthily and this one must be given by families.
Keywords: interview; childhood; school and institutions; education.